EFFICIENCY AND SAFETY OF CHEMOTHERAPY REGIMEN WITH SQ109 IN THOSE SUFFERING FROM MULTIPLE DRUG RESISTANT TUBERCULOSIS - Borisov, S. E.; Bogorodskaya, E. M.; Volchenkov, G. V.; Kulchavenya, E. V.; Maryandyshev, A. O.; Skornyakov, S. N.; Talibov, O. B.; Tikhonov, A. M.; Vasilyeva, I. A. (Tuberkulëz i bolezni lëgkikh, 2018)
The objective of the study: to assess efficiency and safety of SQ109 used within standard treatment regimens for multiple drug resistant tuberculosis (MDR TB)Subjects and Methods A multi-center, double, blind, randomized, placebo-controlled study was conducted in two parallel groups from September 21, 2012 to September 30, 2016, in 6 research centers located in 5 cities of the Russian FederationMain results 1 Cessation of bacillary excretion confirmed by cultures on liquid media by the end of the 6th month of the intensive phase of chemotherapy in pulmonary MDR TB patients receiving SQ109 was observed confidently more often versus treatment regimens containing only existing anti-tuberculosis drugs: both for ITT population (610% versus 429%, p = 00412), and PP population (797% versus 614%, p = 00486) 2 There were no statistically significant differences in the achievement of sputum conversion between the groups, but by the end of the 8th week, the sputum converted in 52% of patients in the group treated with SQ109 versus 38% in the group taking a placebo The median time of bacillary excretion cessation confirmed by culture on liquid media in SQ109 group made 56 days, while in the placebo group it was 84 days 3 Use of SQ109 along with basic chemotherapy for pulmonary MDR TB did not result in the higher frequency of adverse events, worsening of their severity, development of new variants of adverse events compared to the basic anti-tuberculosis treatment of this group of patients in combination with placebo 4 Results of the study allow concluding that SQ109 is an effective drug, satisfactory tolerated (compatible with tolerability of placebo) being a part of integral etiotropic chemotherapy of pulmonary MDR TB patients